The concept of Al-Ta’ayush in Islamic cosmopolitanism: from Medina to Istanbul and Malacca - Abdullah, Asilatul Hanaa (UKM Press, 2021)
In modern Western perspective, Islam is often associated with jihad or holy war waged against non-Muslims. In the Western view, multiculturalism and religious pluralism have neither a place in Islam nor Islamic state, therefore, making Islam look very intolerant and non-inclusive towards other faiths and cultures. This research aims to elucidate how multiculturalism under the concept of Al-Ta’ayush was practised by two Muslim governments, first as manifested in the Millet system (independent court for personal law) under the Ottoman Caliphate and secondly in the Shahbandar (harbourmasters) system under the Malacca Sultanate which later evolved into the Kapitan system. Despite their geographical distance, these systems shared many similarities. This research aims to refute the idea that Islam is intolerant by giving examples from the previous Muslim governments and tracing their systems back to the first Islamic state established by Prophet Muhammad (pbuh), which was the Islamic state of Medina. This paper demonstrates that Muslim rulers during the Ottoman and Malaccan eras were tolerant towards their non-Muslim subjects as shown for instance, in the granting of autonomous rights which enabled the latter to be ruled by their own personal law and to freely practice their own faiths. This practice is unique because first, it was supported by Islamic teachings and secondly, in the pre-modern period where religious and cultural tolerance was not common, Islam was spearheading this concept of Al-Ta’ayush. This consequently makes Islam a religion that celebrates multiculturalism and religious pluralism.